CARACTERIZAÇÃO DA MADEIRA E DA CASCA DE ÁRVORES DE Khaya grandifoliola C. DC. PARA USOS MÚLTIPLOS - Brito, Alice Soares (2021)
The objective of the study was to characterize the physical-mechanical properties of Khaya grandifoliola wood, coming from thinning in commercial plantation at 10 years of age, as well as to evaluate the strength of glued joints of this wood in different glued faces, using four adhesives. The objective was also to produce and physically and mechanically qualify particleboard, homogeneous and mixed, associated with pine wood particles and, finally, to quantify the yield of condensed tannins obtained from the bark of trees, with the addition of two salts, in different concentrations. Five trees were sampled, and discs were removed from them at 1,3 m from the ground (DBH) and at 0, 25, 50, 75 and 100% of the commercial height of each tree to carry out the physical characterization of the wood. Of the 5 trees, the first short piece (base-DBH) was used for mechanical characterization, the third piece (25%-50%) for bonding the joints and the last piece (75-100%) for the production of particleboards. From the disc peels, tannins were extracted. The results showed that the wood of K. grandifoliola studied is of low density, being moderately dimensionally stable and, sometimes, of low mechanical strength. The species showed potential for making glued products, especially on the tangential/radial sides and using the melamine-urea-formaldehyde adhesive. The wood, from thinning, still has promising potential for the production of particleboards, being perceived that the inclusion of african mahogany particles resulted, in general, in panels with greater dimensional stability and better mechanical properties. As for the tannin extraction, the addition of 3% sodium sulfite to the extract provided the best average of condensed tannins, which was equal to 10,07%.